Estudo do efeito da coadministração da quercetina com tamoxifeno na atividade colinergética e antioxidante do hipocampo de ratas ovariectomizadas - Bramatti, Isabella Calvo (2017)
Tamoxifen is classified as a selective estrogen receptor modulator, with much use in the treatment of breast cancer. Quercetin has aroused interest, mainly for its antioxidant action, which may minimize the damage caused by tamoxifen. Due to the lack of studies about the coadministration of quercetin with tamoxifen, the objective of this study was to elucidate the effect upon the cholinergic activity and antioxidante defense. At the study, ovariectomized rats were separated into groups and treated with tamoxifen (5 mg.Kg-1), quercetin (22,5 mg.Kg-1) and the coadministration of tamoxifen (5 mg.Kg-1) plus quercetin (22,5 mg.Kg-1). The hippocampus was isolated and utilized for the determination of acetylcholinesterase and butyrylcholinesterase activity, superoxide dismutase and catalase activity, and the oxidative damage markers (lipid peroxidation and dosage of thiols groups). It was possible observe the oxidant effect of tamoxifen at the hippocampus, where acted like an antagonist at the estrogen receptors, increasing the lipid peroxidation, levels of thiol groups and attenuating catalase activity; in addition to a cholinergic effect, with the decrease of acetylcholinesterase and butyrylcholinesterase activity. When coadministered the quercetin with tamoxifen, it can be seen that at a situation of oxidative stress, the quercetin acts like pro oxidant in the studied.